Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12864-018-4817-4
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly and comparative transcriptome analysis of Monilinia fructicola, Monilinia laxa and Monilinia fructigena, the causal agents of brown rot on stone fruits

Abstract: BackgroundBrown rots are important fungal diseases of stone and pome fruits. They are caused by several Monilinia species but M. fructicola, M. laxa and M. fructigena are the most common all over the world. Although they have been intensively studied, the availability of genomic and transcriptomic data in public databases is still scant. We sequenced, assembled and annotated the transcriptomes of the three pathogens using mRNA from germinating conidia and actively growing mycelia of two isolates of opposite ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 78 publications
0
32
0
Order By: Relevance
“…In agreement with this, a global transcriptomic study of the three most common Monilinia spp. revealed that a PME from M. laxa was included among the differentially expressed transcripts (de Miccolis Angelini et al ., ). Furthermore, this PME ( B. cinerea protein ID: BCIN_03g03830) is coincident with the putative functionally annotated MlPME2 studied in this work.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In agreement with this, a global transcriptomic study of the three most common Monilinia spp. revealed that a PME from M. laxa was included among the differentially expressed transcripts (de Miccolis Angelini et al ., ). Furthermore, this PME ( B. cinerea protein ID: BCIN_03g03830) is coincident with the putative functionally annotated MlPME2 studied in this work.…”
Section: Discussionmentioning
confidence: 97%
“…However, the pivotal role of MfPG1, which diminishes fungal virulence when overexpressed, has also been highlighted (Chou et al, 2015). Among other CWDEs, PMEs and RG-HYDs may be involved in M. laxa pathogenicity, according to recently published transcriptomic data (de Miccolis Angelini et al, 2018). Nevertheless, no other studies have tried to elucidate the putative role that these CAZymes may play in the M. laxa-stone fruit interaction, and thus little evidence is available for their role as virulence determinants in pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The strain was characterized at both the phenotypic and molecular levels (Abate, De Miccolis Angelini, et al. 2018; Abate, Pastore, et al 2018; De Miccolis Angelini et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Our data reduced the M. fructigena assembly to 131 scaffolds without gaps. In addition, the sequence completeness and high coverage were verified by mapping RNA sequencing (RNA-Seq) reads from the same M. fructigena strain [ 7 ]. The availability of a more accurate genome sequence provides improved opportunities to the scientific community for studies aimed at exploring in more detail the pathogen epidemiology, its host interactions, and the tools to optimise brown rot management.…”
Section: Objectivesmentioning
confidence: 99%
“…A monoconidial strain of M. fructigena , Mfrg269, was derived from plum during monitoring of Monilinia populations present on stone fruit in southern Italy (Tursi, Basilicata) [ 8 ]. The strain was characterised both at the phenotypic and molecular levels [ 7 9 ]. The strain was grown in liquid medium (2% malt extract; Oxoid) for 36 h at 24 ± 1 °C, in darkness and under shaking (150 rpm).…”
Section: Data Descriptionmentioning
confidence: 99%